Pengaruh Faktor Budaya Organisasi terhadap Kinerja Pembelajaran Dosen Fakultas Ekonomi - Oemar, Yohanas (Jurnal Aplikasi Manajemen, 2009)
this study was aimed at determining and analyzing the effects of organizational culture, career promotion and job satisfaction on lectors' learning performance at Economic Faculty, University of Riau. Samples taken were of 55 respondents out of 124 people (lectors) as population. Multiple linear regression was used with formulation: Y = bo + b1x1 +b2x2 + b3x3. The results showed that the model might be described as following: Y = 5,041 - 0,733X1 + 0,327X2 - 0,015X3. The study concluded that career and job satisfaction had negative effects on lectors' learning performance. Relationship between independent variable (organizational culture, career promotion and job satisfaction) with independent variable was shown by correlational coefficient (R) of 51,9%.